2022
DOI: 10.3390/su141610227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Influence of Different Layouts of Residential Buildings on the Urban Thermal Environment

Abstract: Urban residential building layouts have an impact on air temperature and thermal comfort. Research has shown that poorly designed building layouts can lead to thermal discomfort. Thus, it is crucial to analyze the relationship between residential building layouts and air temperature. We used the ENVI-met 3D microclimate model to simulate six typical residential building layouts and explore the diurnal and seasonal variations in air temperature. In addition, we used the physiological equivalent temperature (PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Local wind speeds around a building or façade can deviate significantly from the meteorological wind speed. Building layout, building height, building shape, roughness elements, and many other parameters can affect the local wind speeds [63,64]. Although the increase in the meteorological wind gust speed is small (up to 10%), the local wind speed can be amplified, which induces a larger pressure difference across a façade or other elements such as a window.…”
Section: Adhesive Failurementioning
confidence: 99%
“…Local wind speeds around a building or façade can deviate significantly from the meteorological wind speed. Building layout, building height, building shape, roughness elements, and many other parameters can affect the local wind speeds [63,64]. Although the increase in the meteorological wind gust speed is small (up to 10%), the local wind speed can be amplified, which induces a larger pressure difference across a façade or other elements such as a window.…”
Section: Adhesive Failurementioning
confidence: 99%
“…They found that restricting building height could have a negative effect on microclimates, whereas a stepped building height design did not influence thermal comfort. Regarding spatial layout, Yuanyuan Li et al [15] surveyed typical residential area layouts in Beijing and employed simulation software to study their influence on thermal environments. Among the various residential area types in Beijing, their findings indicated that enclosed residential layouts were the most optimal.…”
Section: Introductionmentioning
confidence: 99%